2021
DOI: 10.1029/2021ja029582
|View full text |Cite
|
Sign up to set email alerts
|

The Polar Cusp Seen by Cluster

Abstract: The investigation of the magnetospheric polar cusps was one of the main objectives of the Cluster mission. The four satellites have crossed those regions numerous times over the years and, with their suitable instrumentation, favorable orbits, and unique multipoint measurements, many aspects of the cusp have been unveiled. The first of those is its highly dynamic nature. With four satellites, whatever their altitude and thus their configuration, the spatial/temporal ambiguity has been lifted and a completely n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 261 publications
(501 reference statements)
1
19
0
Order By: Relevance
“…The boundary between the cusp and magnetosheath also becomes indented (compare the |v i | contours in Figures 9 and 11). This is consistent with observations which show indentations of the cusp boundary (Pitout & Bogdanova, 2021;Zhang et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…The boundary between the cusp and magnetosheath also becomes indented (compare the |v i | contours in Figures 9 and 11). This is consistent with observations which show indentations of the cusp boundary (Pitout & Bogdanova, 2021;Zhang et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Some authors suggested that dB/dt spikes in the local morning sector could alternatively be associated with Pc5 pulsations generated by the Kelvin‐Helmholtz instability (KHI; Kataoka et al., 2001; Ngwira et al., 2018; Pulkkinen & Kataoka, 2006; Weigel et al., 2003) or by upstream ion‐cyclotron resonance (Howard & Menk, 2005) on the morning flank of the magnetopause. However, we do not believe this explanation because any processes at the magnetopause, including KHI (independently of their scale), would magnetically map very close to the vicinity of the dayside cusp, that is, not much further than 08–09 MLT into the dawn sector, as the longitudinal variability of the cusp in response to solar wind forcing is not more than three to maximum of 4 hr from local noon (Pitout & Bogdanova, 2021). Thus, it appears very difficult to connect the ionospheric current features caused by the KHI at the flanks with our observations in the morning sector at 05–06 MLT.…”
Section: Discussionmentioning
confidence: 93%
“…Some authors suggested that dB/dt spikes in the local morning sector could alternatively be associated with Pc5 pulsations generated by the Kelvin-Helmholtz instability (KHI; Kataoka et al, 2001;Ngwira et al, 2018;Pulkkinen & Kataoka, 2006;Weigel et al, 2003) or by upstream ion-cyclotron resonance (Howard & Menk, 2005) on the morning flank of the magnetopause. However, we do not believe this explanation because any processes at the magnetopause, including KHI (independently of their scale), would magnetically map very close to the vicinity of the dayside cusp, that is, not much further than 08-09 MLT into the dawn sector, as the longitudinal variability of the cusp in response to solar wind forcing is not more than three to maximum of 4 hr from local noon (Pitout & Bogdanova, 2021). Thus, it appears very difficult to connect the ionospheric current features caused by the KHI at the flanks with our observations in the morning sector at 05-06 MLT.…”
Section: Ionospheric Phenomena Related To the Hotspotsmentioning
confidence: 85%